Increase of Yield, Lycopene, and Lutein Content in Tomatoes Grown Under Continuous PAR Spectrum LED Lighting - Dannehl, Dennis; Schwend, Thomas; Veit, Daniel; Schmidt, Uwe (Frontiers in Plant Science, 2021)
Light emitting diodes (LEDs) are an energy efficient alternative to high-pressure sodium (HPS) lighting in tomato cultivation. In the past years, we have learned a lot about the effect of red and blue LEDs on plant growth and yield of tomatoes. From previous studies we know that plants absorb and utilize most of the visible spectrum for photosynthesis. This part of the spectrum is referred to the photosynthetically active radiation (PAR). We designed a LED fixture with an emission spectrum that partially matches the range of 400 to 700 nm and thus partially covers the absorption spectrum of photosynthetic pigments in tomato leaves. Tomato plants grown under this fixture were significantly taller and produced a higher fruit yield (14%) than plants grown under HPS lighting. There was no difference in number of leaves and trusses, leaf area, stem diameter, the electron transport rate, and the normalized difference vegetation index. Lycopene and lutein content in tomatoes was 18% and 142% higher when they were exposed to the LED fixture. However, the ß-carotene content was not different between the light treatments. Transpiration rate under LED was significantly lower (40%) while the light use efficiency (LUE) was significantly higher (19%) compared to HPS lighting. This data show that an LED fixture with an emission spectrum covering the entire PAR range can improve LUE, yields and content of secondary metabolites in tomatoes compared to HPS lighting.